2019
DOI: 10.2147/opth.s196622
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation between body mass index and ocular parameters</p>

Abstract: Purpose: To investigate the relationship between BMI and selected ocular parameters. Subjects and methods: Fifty-three left eyes of normal weight subjects and 67 age-sex matched overweight subjects were studied. Inclusion criteria for the normal weight and overweight groups included BMI between 18.5–22.9 and 23.0–29.9 kg/m 2 , respectively. Subjects with a history of systemic disease, ocular disease or surgery, or disability were excluded. All subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…In addition to the studies indicating that the CT among obese subjects is not different from those of the normal population,[ 23 ] contrasting studies are postulating that CT is thinner in obese subjects. [ 8 9 24 ] CT measurements can be affected by many factors, such as age, gender, ethnicity, axial length, diurinal variations, and coffee and cigarette dependence, which may account for the differences between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the studies indicating that the CT among obese subjects is not different from those of the normal population,[ 23 ] contrasting studies are postulating that CT is thinner in obese subjects. [ 8 9 24 ] CT measurements can be affected by many factors, such as age, gender, ethnicity, axial length, diurinal variations, and coffee and cigarette dependence, which may account for the differences between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no significant differences were found between the measurements taken of central macula thickness, subfoveal choroidal thickness, mean peripapillary retinal nerve fiber layer thickness, superior peripapillary retinal nerve fiber layer thickness, inferior peripapillary retinal nerve fiber layer thickness, nasal peripapillary retinal nerve fiber layer thickness and temporal peripapillary retinal nerve fiber layer thickness between the study group and the control group. It is interesting to note that there are studies that describe a decrease in the subfoveal choroidal thickness [9], a decrease in the thickness of the retinal nerve fiber layer [9] [11] and an increase in macular thickness [8] in obese individuals. It is possible that these findings are due to samples with different characteristics such as refractive errors, for example.…”
Section: Discussionmentioning
confidence: 99%
“…All systemic parameters (BMI, BGL, SBP, and DBP) were significantly higher in men than in women, possibly mediating some of our sex differences in ocular biometrics. Our trends for higher IOP in men could have been due to higher BMI and BGL levels, which have both been found to positively correlate with IOP [ 25 , 28 ]. The role of BP in the regulation of IOP is complex, and some studies have shown that BP increases of 40 mmHg are only accompanied by IOP increases of 1 mmHg (reviewed by He et al [ 66 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, previous authors have also demonstrated associations between body mass index (BMI) and both IOP [ 25 ] and CCT [ 26 , 27 ]. Others have shown positive relationships between blood glucose levels (BGL) and IOP [ 28 ], CCT [ 27 ] and, more equivocally, FT [ 29 ].…”
Section: Introductionmentioning
confidence: 99%